2006
DOI: 10.1111/j.1365-2265.2006.02469.x
|View full text |Cite
|
Sign up to set email alerts
|

The influences of hyperprolactinemia and obesity on cardiovascular risk markers: effects of cabergoline therapy

Abstract: These data suggest that hyperprolactinaemia is associated with insulin resistance related to increased BMI and low-grade inflammation independently of BMI. Short-term cabergoline therapy can reduce the inflammatory markers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

7
119
6
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 128 publications
(133 citation statements)
references
References 23 publications
7
119
6
1
Order By: Relevance
“…Cabergoline was superior to bromocriptine in affecting 2-hr post-challenge plasma glucose levels, HOMA-IR, as well as circulating levels of IGF-1, FFA, uric acid, hsCRP, homocysteine, fibrinogen and 25-hydroxyvitamin D. Our results may suggest that cabergoline is superior to bromocriptine when it comes to affecting atherogenic dyslipidaemia, insulin sensitivity and circulating levels of cardiovascular risk factors in hyperprolactinaemic patients. These findings seem to support previous observations that cabergoline may be a better treatment for patients with elevated prolactin levels than bromocriptine.Apart from oligomenorrhea, infertility, galactorrhoea, loss of libido and sexual dysfunction, long-term prolactin excess is often complicated by impaired glucose tolerance, hyperinsulinaemia, insulin resistance, atherogenic dyslipidaemia, subclinical atherosclerosis, endothelial dysfunction and weight gain [1][2][3][4][5][6][7][8]. These abnormalities may be alleviated or reversed by dopamine agonists, being the drugs of choice in the treatment of prolactin-secreting tumours and elevated prolactin levels secondary to other disorders [9].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Cabergoline was superior to bromocriptine in affecting 2-hr post-challenge plasma glucose levels, HOMA-IR, as well as circulating levels of IGF-1, FFA, uric acid, hsCRP, homocysteine, fibrinogen and 25-hydroxyvitamin D. Our results may suggest that cabergoline is superior to bromocriptine when it comes to affecting atherogenic dyslipidaemia, insulin sensitivity and circulating levels of cardiovascular risk factors in hyperprolactinaemic patients. These findings seem to support previous observations that cabergoline may be a better treatment for patients with elevated prolactin levels than bromocriptine.Apart from oligomenorrhea, infertility, galactorrhoea, loss of libido and sexual dysfunction, long-term prolactin excess is often complicated by impaired glucose tolerance, hyperinsulinaemia, insulin resistance, atherogenic dyslipidaemia, subclinical atherosclerosis, endothelial dysfunction and weight gain [1][2][3][4][5][6][7][8]. These abnormalities may be alleviated or reversed by dopamine agonists, being the drugs of choice in the treatment of prolactin-secreting tumours and elevated prolactin levels secondary to other disorders [9].…”
mentioning
confidence: 99%
“…Apart from oligomenorrhea, infertility, galactorrhoea, loss of libido and sexual dysfunction, long-term prolactin excess is often complicated by impaired glucose tolerance, hyperinsulinaemia, insulin resistance, atherogenic dyslipidaemia, subclinical atherosclerosis, endothelial dysfunction and weight gain [1][2][3][4][5][6][7][8]. These abnormalities may be alleviated or reversed by dopamine agonists, being the drugs of choice in the treatment of prolactin-secreting tumours and elevated prolactin levels secondary to other disorders [9].…”
mentioning
confidence: 99%
“…Lipid abnormalities such as, hypercholesterolemia, hypertriglyceridemia and normal lipid profiles are reported in prolactinoma patients [14,18,19]. Some studies have suggested the influence of hyperprolactiemia on the lipid profile but the mechanism is not well established.…”
Section: Discussionmentioning
confidence: 99%
“…It is suggested that obesity is occurs secondary to the changing in hypothalamic energy metabolism [13]. But, direct relationship between high prolactin and BMI is not clear [14]. A reduction in dopaminergic tone [5,15]; leptin resistance [5]; decreased adiponectin levels [16] and hypogonadism [17] are also hypothesized to be contributing factors on weight gain in patients with prolactinoma.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation